The lower river - Theroux, Paul (Houghton Mifflin Harcourt, 2012)
Ellis Hock never believed that he would return to Africa. He runs an old-fashioned menswear store in a small town in Massachusetts but still dreams of his Eden, the four years he spent in Malawi with the Peace Corps, cut short when he had to return to take over the family business. When his wife leaves him, and he is on his own, he realizes that there is one place for him to go: back to his village in Malawi, on the remote Lower River, where he can be happy again. Arriving at the dusty village, he finds it transformed: the school he built is a ruin, the church and clinic are gone, and poverty and apathy have set in among the people. They remember him--the White Man with no fear of snakes--and welcome him. But is his new life, his journey back, an escape or a trap?